2009
DOI: 10.1002/cpp.611
|View full text |Cite
|
Sign up to set email alerts
|

Rumination, goal linking, daily hassles and life events in major depression

Abstract: Background: Rumination in response to stressful events and depressed mood leads to harmful

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
2
21
0
8
Order By: Relevance
“…It is hypothesised that a decrease in rumination or an increase in self-compassion or mindfulness may mediate improvements following MBCT in depression (Raes et al 2009;McIntosh et al 2010;Pauley & McPherson, 2010). In this study, significant associations were found between increases in self-compassion and mindfulness and decreases in measures of depression and anxiety, in line with the above hypothesis.…”
Section: Discussionsupporting
confidence: 80%
“…It is hypothesised that a decrease in rumination or an increase in self-compassion or mindfulness may mediate improvements following MBCT in depression (Raes et al 2009;McIntosh et al 2010;Pauley & McPherson, 2010). In this study, significant associations were found between increases in self-compassion and mindfulness and decreases in measures of depression and anxiety, in line with the above hypothesis.…”
Section: Discussionsupporting
confidence: 80%
“…Although hassles, considered individually, may be viewed as inconsequential to well-being, cumulatively, they may have marked adverse effects Downloaded by [Stony Brook University] at 14:57 13 October 2014 (McIntosh, Gillanders, & Rodgers, 2010;Pettit, Lewinsohn, Seeley, Roberts, & Yaroslavsky, 2010). Moreover, when these daily annoyances are superimposed on the backdrop of a severe or chronic stressor, their role in promoting poor well-being becomes especially pronounced (Henderson, Roberto, & Kamo, 2001;Serido et al, 2004).…”
Section: Daily Hassles Uplifts and Coping Strategiesmentioning
confidence: 94%
“…Depresyonun epidemiyolojisiyle ilgili çalışmalar-da genel olarak varılan ortak sonuç, depresyonun sıklığının ve yaygınlığının kadınlarda erkeklerden daha yüksek oranda şeklindedir. Çeşitli çalışmalarda kadınlarda MDB riski erkeklerin 2 katı olarak saptanmıştır (10)(11)(12)(13)(14). Ancak yaş ilerledikçe kadın ile erkek arasındaki bu fark azalmaktadır.…”
Section: Major Depresi̇f Bozukluk Epi̇demi̇yoloji̇si̇unclassified
“…Depresif bozukluklar yaşamları süresince erkeklerin %5-12'sini, kadınların ise %10-25'ini etkilemektedir (15). MDB'nin kadınlarda erkeklerin 2 katı olmasının nedenleri olarak hormonal farklılıklar, genetik duyarlılık ya da MAO yüksek-liği ve tirod hastalıkları, menstruasyon gibi biyolojik etmenler yanında, çocukluğundan itibaren şiddete maruz kalma, girişken olma yönünden baskılanma, boyun eğen, pasif ve bağımlı olmayı öğrenme, kadına verilen toplumsal roller ve ondan beklentiler (ev işleri, çocuk doğurma, çocuk yetiştirme, eşe karşı sorumluluklar), düşük eği-tim ve gelir olanakları, işsizlik, düşük sosyoekonomik düzey, ayrımcılığa maruz kalma gibi riskler gösterilmektedir (13,14,(16)(17)(18)(19).…”
Section: Major Depresi̇f Bozukluk Epi̇demi̇yoloji̇si̇unclassified
See 1 more Smart Citation